2004
DOI: 10.1158/1078-0432.ccr-03-0591
|View full text |Cite
|
Sign up to set email alerts
|

Flat-Fixed Dosing of Irinotecan

Abstract: Purpose: In a previous analysis, it was shown that bodysurface area (BSA) is not a predictor of irinotecan pharmacokinetic parameters. Here, we prospectively evaluated the effects of administering a flat-fixed irinotecan dose to cancer patients, regardless of BSA.Experimental Design: Twenty-six cancer patients (12 females) received a fixed irinotecan dose of 600 mg, given as a 90-min i.v. infusion. Plasma concentrations of irinotecan and its metabolites SN-38 (7-ethyl-10-hydroxycamptothecin) and SN-38G (SN-38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 18 publications
2
35
0
1
Order By: Relevance
“…As a result, the interindividual pharmacokinetic variability of irinotecan and its active metabolite SN-38 were 19% to 25% lower in the equation-based dosing group, whereas the dose range was substantially broader in this group. In line with the known association between irinotecan pharmacokinetics and drug-related toxicities (5,8,18), a >4-fold reduction of severe myelosuppression was observed in the equationbased dosing group as compared with the other group.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As a result, the interindividual pharmacokinetic variability of irinotecan and its active metabolite SN-38 were 19% to 25% lower in the equation-based dosing group, whereas the dose range was substantially broader in this group. In line with the known association between irinotecan pharmacokinetics and drug-related toxicities (5,8,18), a >4-fold reduction of severe myelosuppression was observed in the equationbased dosing group as compared with the other group.…”
Section: Discussionsupporting
confidence: 65%
“…The conventional dose calculation of irinotecan is based on an individual's body surface area (BSA), although this approach does not result in reduced pharmacokinetic variability ( Fig. 2A) compared with a flat-fixed dose (7,8). New dosing strategies that take the pharmacologic profile of irinotecan in the individual patient into account could potentially replace BSA-based dosing, if this would lead to a reduction in the pharmacokinetic variability.…”
mentioning
confidence: 99%
“…The interindividual variability in irinotecan and SN-38 pharmacokinetic parameters is large and has been associated with variation in its clinical outcome and toxicity profiles (25). Previous investigations have demonstrated that body surface area is an unimportant factor in explaining this variability (29). The interindividual variability in SN-38 pharmacokinetics is more likely related to a host of other factors, including hepatic function (30) and use of concomitant medication (31) in addition to multiple polymorphic pathways involved in the excretion and biotransformation of irinotecan.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were treated with single-agent irinotecan once every 3 weeks over 90 minutes at a dose of 350 mg/m 2 , its 600 mg flat-fixed (irrespective of BSA) dose equivalent [32,33], or at a dose that was based on cytochrome P450 (CYP)3A4 phenotyping [34] were studied during their first treatment course. Premedication consisted of dexamethasone and granisetron.…”
Section: Patients and Treatmentmentioning
confidence: 99%